2020
DOI: 10.1111/head.14015
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and Sport in a Physically Active Population of Students: Results of a Cross‐Sectional Study

Abstract: Objective In this study, we explored the relationship between migraine and sport in a physically active population of students, analyzing the risk of migraine among sporty students. Background The relationship between sport and migraine is controversial; moreover, several studies report on sport as a migraine trigger, but there is evidence that physical activity could have a relevant role in migraine prevention. Methods A cross‐sectional survey was conducted using the validated ID‐migraine questionnaire includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
(115 reference statements)
0
11
0
2
Order By: Relevance
“…This parameter is important, as recently demonstrated during the pandemic when both physical activity levels and sleep quality dropped in migraine patients [ 23 ]. The link between oxidative stress, physical activity, and sleep quality could somehow reside in the CGRP system [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter is important, as recently demonstrated during the pandemic when both physical activity levels and sleep quality dropped in migraine patients [ 23 ]. The link between oxidative stress, physical activity, and sleep quality could somehow reside in the CGRP system [ 12 , 13 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic changes related to neurotransmitters concentration, physical ac-tivity, and the associated oxidative stress are important fields of investigation in mi-graine to achieve this goal [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As we mentioned before, weight loss after bariatric surgery may be beneficial in reducing the duration and severity of migraine attacks, and even in preventing them ( 128 , 129 ). Moreover, several studies have reported that weight loss related to lifestyle sliming strategies, such as physical activity and exercise and/or sports help reduce the frequency of migraine attacks or might exert a protective effect on individuals who suffer from it ( 145 147 ). Nevertheless, the specific role of exercise in migraine is still unclear, especially when considering that both the frequency and intensity of exercise/sports can also trigger migraine attacks ( 146 ).…”
Section: Association Of Migraine and Obesitymentioning
confidence: 99%
“…Nevertheless, the specific role of exercise in migraine is still unclear, especially when considering that both the frequency and intensity of exercise/sports can also trigger migraine attacks ( 146 ). Therefore, further studies are needed to understand the association between sports and migraine ( 147 ), keeping in mind the study limitations and confounding factors.…”
Section: Association Of Migraine and Obesitymentioning
confidence: 99%
“…It is a well-known fact that inactivity and sedentarism can lead to early specific alterations in the skeletal muscle [19][20][21][22]. In particular, high intensity PA is reported as a precipitant factor for migraine [23], while regular and moderate PA show a protective role in such patients [24,25]. Thus, Varkey et al (2008) showed a strong linear trend of higher prevalence of low PA with increasing headache frequency [26].…”
Section: Introductionmentioning
confidence: 99%